Molybdenum disulfide-MXene / biomass carbon composite aerogel as well as preparation method and application thereof
By growing molybdenum disulfide in biomass carbon aerogel and electrostatically assembled with MXene, a molybdenum disulfide-MXene/biomass carbon composite aerogel adsorbent was constructed, which solved the difficulty of removing cesium ions and strontium ions in nuclear wastewater, and achieved efficient adsorption and solar seawater desalination.
Patent Information
- Application Number
- CN202510442282.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2025-06-13
- Estimated Expiration
- 2045-04-09
AI Technical Summary
In the radioactive wastewater generated during nuclear energy utilization, it is difficult to remove and recover cesium and strontium ions, especially in seawater, the complexity of treatment is increased due to the presence of competitive ions.
Molybdenum disulfide-MXene/biomass carbon composite aerogel is used as the adsorbent, and molybdenum disulfide is grown in the biomass carbon aerogel by hydrothermal method, and MXene is added through electrostatic assembly to construct a photothermal nanocomposite adsorption agent, which uses photothermal effect to improve the adsorption kinetic efficiency.
It achieves efficient enrichment and selective adsorption of cesium ions and strontium ions, improves adsorption kinetic efficiency, and can achieve seawater desalination under the action of solar energy.
Smart Images

Figure CN120132813A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aerogels, and particularly relates to a molybdenum disulfide-MXene / biomass carbon composite aerogel and a preparation method and application thereof. Background Art
[0002] The environmental pollution problems caused by the combustion of fossil fuels globally and the sharp increase in the demand for energy have promoted the urgent development of nuclear energy. However, it is worrying that radioactive waste will inevitably be generated during the utilization of nuclear energy, and the resulting nuclear pollution problems cannot be ignored. Among them, cesium-137 (emitting γ rays) and strontium-90 (emitting β rays) are considered to be the main sources of radioactivity and the substances with the highest safety risks in nuclear waste due to their long half-lives. In addition, most nuclear power plants are built by the sea. Once leaked, it will have a serious impact on the marine environment, and the ocean contains a large amount of Na + , K + , Ca 2+ , Mg 2+ , Fe 3+ , Al 3+ and other competitive ions, increasing the difficulty of wastewater treatment. Therefore, it is of great significance for the post-treatment of radioactive nuclear wastewater to efficiently and selectively remove and recover cesium ions and strontium ions from seawater with complex and diverse compositions and properties.
[0003] The adsorption method has become an effective method for removing radioactive nuclides such as cesium ions and strontium ions due to its advantages of low cost and convenient operation. The soft base ion S in the molybdenum disulfide structure 2- has strong affinity and selectivity for soft acid ions such as cesium ions and strontium ions, and has become a promising type of radioactive nuclide adsorbent. However, traditional adsorption methods generally mainly rely on passive adsorption, and the adsorption rate is generally low. Solar interfacial evaporation technology is a new type of solar photothermal evaporation technology based on interfacial phase change, which shows great application prospects in seawater desalination and wastewater treatment. Biomass carbon aerogel exhibits low density, three-dimensional porous network structure and biodegradability, and can achieve efficient water transport and evaporation under capillary action, and is a good supporting layer material for solar interfacial evaporation. MXene is a new type of two-dimensional flake material, which has unique two-dimensional surface characteristics, a large number of active functional groups (-O, -OH and -F, etc.) and a high specific surface area, and has been widely used in the fields of adsorption and seawater desalination. In addition, the internal photothermal conversion efficiency of MXene is close to 100%, and it has been proved to be an excellent photothermal conversion material. Summary of the Invention
[0004] In view of this, the purpose of the present invention is to provide a molybdenum disulfide-MXene / biomass carbon composite aerogel, its preparation method and application. The composite aerogel has good light absorption and conversion capabilities, promotes the enrichment of radioactive cesium ions and strontium ions by the adsorption material, improves its adsorption kinetic efficiency, and can simultaneously realize solar desalination of seawater. As an adsorption material, the composite aerogel can exhibit high adsorption, high selectivity and high stability, and has good market application prospects.
[0005] The technical solution adopted is as follows:
[0006] First aspect, a preparation method of a molybdenum disulfide-MXene / biomass carbon composite aerogel of the present invention includes the following steps:
[0007] (1) Preparation of biomass carbon aerogel: Chitosan is dispersed in an acetic acid solution, stirred and dissolved to obtain a chitosan dispersion solution, waste leather shavings hydrolyzate is added and stirred evenly, and then a glutaraldehyde cross-linking agent is added for cross-linking reaction to obtain a chitosan hydrogel, which is freeze-dried to obtain a chitosan aerogel; then the chitosan aerogel is pyrolyzed in a tube furnace at 400-800 °C under an inert gas atmosphere to obtain a biomass carbon aerogel;
[0008] (2) Preparation of molybdenum disulfide / biomass carbon composite aerogel: The biomass carbon aerogel prepared in step (1) is immersed in a mixed solution of ammonium molybdate tetrahydrate and thiourea, and then sodium citrate is added, and it is placed in a reaction kettle for hydrothermal reaction at 160-220 °C to obtain a molybdenum disulfide / biomass carbon composite aerogel;
[0009] (3) Preparation of molybdenum disulfide-MXene / biomass carbon composite aerogel: First, MXene is added to deionized water and ultrasonically dispersed to obtain an MXene dispersion solution, and poly(diallyldimethylammonium chloride) is added to positively modify MXene, and then the molybdenum disulfide / biomass carbon composite aerogel prepared in step (2) is impregnated in the modified MXene dispersion solution to obtain a molybdenum disulfide-MXene / biomass carbon composite aerogel.
[0010] Among them, the waste leather shavings hydrolyzate can be prepared by the following method, including the following steps:
[0011] First pretreatment: Weigh 25-30 g of wet blue sheepskin waste leather shavings, then add 250-300 g of water, 12-15 g of sulfuric acid, 25-30 g of oxalic acid, stir in a water bath at 30-35 °C for 6-7 h, filter and collect the product, and store it in a refrigerator for refrigeration;
[0012] Second pretreatment: Add the product collected after the first pretreatment to 300 - 350 g of water, 16 - 20 g of sulfuric acid, and 25 - 30 g of oxalic acid, stir in a water bath at 30 - 35 °C for 6 - 7 h, filter by suction, collect the product, and store it in a refrigerator for preservation;
[0013] Acid hydrolysis and extraction: Add the product collected after the second pretreatment to 100 - 150 g of water and 9 - 12 g of glacial acetic acid, stir in a water bath at 70 - 75 °C for 6 - 7 h to obtain a waste leather shaving hydrolysis solution. Add sodium chloride for salting - out in the waste leather shaving hydrolysis solution, let it stand, collect the waste leather shaving hydrolyzate, and dry it for later use. Or prepare it according to the preparation method of the waste leather shaving hydrolyzate in CN 112853746A and then use it for later use.
[0014] Further, in step (1), the mass ratio of chitosan to the waste leather shaving hydrolyzate is (3 - 10):1.
[0015] Further, in step (2), the mass ratio of ammonium molybdate tetrahydrate to thiourea is 1:(1 - 5); and / or, the ratio of the mass of the biomass carbon aerogel to the sum of the masses of ammonium molybdate tetrahydrate and thiourea is 1:(30 - 110).
[0016] Further, in step (2), the mass ratio of the biomass carbon aerogel to sodium citrate is 1:(0.5 - 1.5).
[0017] Further, in step (3), the concentration of the MXene dispersion is 0.01 - 3 mg / L.
[0018] Further, in step (2), the solid - liquid ratio of the mixed solution of ammonium molybdate tetrahydrate and thiourea is 1 g:(20 - 50) mL; and / or, in step (3), the solid - liquid ratio of the molybdenum disulfide / biomass carbon composite aerogel to the modified MXene dispersion is 1 g:(50 - 100) mL.
[0019] Further, in step (1), place the chitosan aerogel in a tube furnace and pyrolyze it at 400 - 800 °C under a N 2 atmosphere at a heating rate of 5 °C·min -1 for 2 - 8 h.
[0020] Second, a molybdenum disulfide - MXene / biomass carbon composite aerogel of the present invention is prepared by the preparation method described in the above - mentioned scheme.
[0021] Third, an adsorbent of the present invention includes the molybdenum disulfide - MXene / biomass carbon composite aerogel described in the above - mentioned scheme.
[0022] Fourth aspect, application of the molybdenum disulfide-MXene / biomass carbon composite aerogel described in the above solution in the treatment of radioactive wastewater containing cesium ions and strontium ions.
[0023] In the above technical solution,
[0024] First, the biomass carbon aerogel is immersed in a mixed solution of a sulfur source and a molybdenum source, and molybdenum disulfide is in-situ grown on the biomass carbon aerogel by a hydrothermal method to obtain a uniformly loaded molybdenum disulfide / biomass carbon composite aerogel, and sodium citrate is added to induce the vertical growth of molybdenum disulfide in the biomass carbon aerogel. Then, the molybdenum disulfide / biomass carbon composite aerogel and MXene are electrostatically assembled to obtain a molybdenum disulfide-MXene / biomass carbon composite aerogel. This composite aerogel has good photothermal absorption and conversion capabilities, promotes the enrichment of radioactive cesium ions and strontium ions by the adsorbent, improves its adsorption kinetic efficiency, and can simultaneously achieve solar desalination of seawater.
[0025] That is, the present invention controllably assembles molybdenum disulfide, MXene and biomass carbon aerogel to construct a material for highly selectively adsorbing cesium ions and strontium ions, combines the solar interface evaporation technology with the adsorption method, and uses the photothermal effect to improve the adsorption kinetic efficiency of the adsorbent for cesium ions and strontium ions, and simultaneously realizes solar desalination of seawater.
[0026] Therefore, the beneficial effects of the present invention are as follows:
[0027] 1. In the present invention, molybdenum disulfide nanosheets are in-situ grown on the biomass carbon aerogel by a hydrothermal method, and sodium citrate is added to induce the uniform vertical growth of molybdenum disulfide in the biomass carbon aerogel. The biomass carbon aerogel can maintain its unique three-dimensional network porous structure, which is beneficial for cesium ions and strontium ions to quickly enter the internal structure of the composite adsorbent, and realize the selective adsorption of cesium ions and strontium ions through the active sites on the molybdenum disulfide grown on the biomass carbon aerogel.
[0028] 2. In the present invention, the controllable assembly of the molybdenum disulfide / biomass carbon composite aerogel and MXene is realized through electrostatic interaction to construct a photothermal type nano-composite adsorbent. The local heat generated by the photothermal effect of the system can promote the adsorption of the adsorbent for cesium ions and strontium ions, improve its adsorption kinetic efficiency, realize the synergistic regulation of the adsorption performance and photothermal performance of the system, and can simultaneously achieve solar desalination of seawater.
[0029] 3. In the present invention, the selected materials are widely sourced and low-cost, realizing the high-value utilization of waste resources. The prepared molybdenum disulfide-MXene / biomass carbon composite aerogel does not cause secondary pollution to the environment, is easy to recycle and can be reused, and is a very promising material for treating radioactive wastewater. Description of the Drawings
[0030] Figure 1 XRD pattern of the molybdenum disulfide-MXene / biomass carbon composite aerogel prepared in Example 1 of the present invention;
[0031] Figure 2 Scanning electron microscope image of the molybdenum disulfide-MXene / biomass carbon composite aerogel prepared in Example 1 of the present invention;
[0032] Figure 3 Transmission electron microscope image of the molybdenum disulfide-MXene / biomass carbon composite aerogel prepared in Example 1 of the present invention;
[0033] Figure 4 Adsorption efficiency graph of the molybdenum disulfide-MXene / biomass carbon composite aerogel prepared in Example 1 of the present invention for cesium ions;
[0034] Figure 5 Adsorption efficiency graph of the molybdenum disulfide-MXene / biomass carbon composite aerogel prepared in Example 1 of the present invention for strontium ions. Detailed implementation manners
[0035] The present invention will be described in detail below through specific examples. However, the uses and purposes of these exemplary embodiments are only used to illustrate the present invention, and do not constitute any form of limitation to the actual protection scope of the present invention, nor will the protection scope of the present invention be limited thereto.
[0036] Example 1
[0037] A preparation method of a molybdenum disulfide-MXene / biomass carbon composite aerogel in this example includes the following steps:
[0038] (1) Preparation of biomass carbon aerogel: Dissolve 0.5 g of chitosan in 50 mL of 0.5 mol / L acetic acid solution, stir and dissolve at 80 °C to obtain a chitosan dispersion solution, add 0.1 g of waste leather shavings hydrolyzate and stir evenly, then add 1 mL of 5 wt% glutaraldehyde cross-linking agent for cross-linking reaction to obtain a chitosan hydrogel, and obtain a chitosan-based aerogel by freeze-drying. Then place the chitosan-based aerogel in a tube furnace at 800 °C and N 2 atmosphere at a heating rate of 5 °C·min -1 for 6 h of pyrolysis to obtain a biomass carbon aerogel;
[0039] (2) Preparation of molybdenum disulfide / biomass carbon composite aerogel: Immerse 0.03 g of the biomass carbon aerogel prepared in step (1) in 20 mL of a mixed solution containing 0.6 g of ammonium molybdate tetrahydrate and 1.6 g of thiourea, then add 0.021 g of sodium citrate, place it in a reaction kettle and carry out a hydrothermal reaction at 200 °C for 24 h to obtain a molybdenum disulfide / biomass carbon composite aerogel;
[0040] (3) Preparation of molybdenum disulfide-MXene / biomass carbon composite aerogel: First, 0.5 mg of MXene was added to 5 mL of deionized water and dispersed by ultrasonic to obtain an MXene dispersion. 0.25 mg of polydiallyldimethylammonium chloride was added to positively modify MXene. Then, 0.2 g of the molybdenum disulfide / biomass carbon composite aerogel prepared in step (2) was impregnated in 20 mL of the modified MXene dispersion to obtain the molybdenum disulfide-MXene / biomass carbon composite aerogel.
[0041] Example 2
[0042] A preparation method of a molybdenum disulfide-MXene / biomass carbon composite aerogel in this example includes the following steps:
[0043] (1) Preparation of biomass carbon aerogel: 0.5 g of chitosan was dispersed in 50 mL of 0.5 mol / L acetic acid solution and stirred and dissolved at 80 °C to obtain a chitosan dispersion. 0.2 g of waste leather shavings hydrolyzate was added and stirred evenly. Subsequently, 0.6 mL of 5 wt% glutaraldehyde cross-linking agent was added for cross-linking reaction to obtain a chitosan hydrogel, and the chitosan-based aerogel was obtained by freeze-drying. Then, the chitosan-based aerogel was pyrolyzed in a tube furnace at 600 °C under N 2 atmosphere at a heating rate of 5 °C·min -1 for 8 h to prepare the biomass carbon aerogel;
[0044] (2) Preparation of molybdenum disulfide / biomass carbon composite aerogel: 0.03 g of the biomass carbon aerogel prepared in step (1) was immersed in 20 mL of a mixed solution containing 0.6 g of ammonium molybdate tetrahydrate and 0.9 g of thiourea. Then, 0.021 g of sodium citrate was added, and it was placed in a reaction kettle for hydrothermal reaction at 200 °C for 24 h to obtain the molybdenum disulfide / biomass carbon composite aerogel;
[0045] (3) Preparation of molybdenum disulfide-MXene / biomass carbon composite aerogel: First, 0.1 mg of MXene was added to 5 mL of deionized water and dispersed by ultrasonic to obtain an MXene dispersion. 0.1 mg of polydiallyldimethylammonium chloride was added to positively modify MXene. Then, 0.2 g of the molybdenum disulfide / biomass carbon composite aerogel prepared in step (2) was impregnated in 20 mL of the modified MXene dispersion to obtain the molybdenum disulfide-MXene / biomass carbon composite aerogel.
[0046] Example 3
[0047] A preparation method of a molybdenum disulfide-MXene / biomass carbon composite aerogel in this example includes the following steps:
[0048] (1) Preparation of biomass carbon aerogel: 0.5 g chitosan was dispersed in 50 mL 0.5 mol / L acetic acid solution, stirred and dissolved at 80 °C to obtain a chitosan dispersion, 0.3 g of waste leather hydrolyzate was added and stirred evenly, then 1.2 mL 5 wt% glutaraldehyde crosslinking agent was added to perform a crosslinking reaction to obtain chitosan hydrogel, and chitosan-based aerogel was obtained by freeze drying. The chitosan-based aerogel was then heated in a tubular furnace at 800 °C, N 2 At 5℃·min -1 The biomass carbon aerogel was obtained by pyrolysis at a heating rate of 8h.
[0049] (2) Preparation of molybdenum disulfide / biomass carbon composite aerogel: 0.03 g of the biomass carbon aerogel prepared in step (1) was soaked in 20 mL of a mixed solution containing 0.6 g of ammonium molybdate tetrahydrate and 2.6 g of thiourea, and then 0.021 g of sodium citrate was added, and the mixture was placed in a reactor and subjected to hydrothermal reaction at 180° C. for 18 h to obtain a molybdenum disulfide / biomass carbon composite aerogel;
[0050] (3) Preparation of molybdenum disulfide-MXene / biomass carbon composite aerogel: First, 1 mg of MXene was added to 5 mL of deionized water and ultrasonically dispersed to obtain a MXene dispersion, 0.8 mg of polydiallyldimethylammonium chloride was added to positively modify the MXene, and then 0.2 g of the molybdenum disulfide / biomass carbon composite aerogel prepared in step (2) was immersed in 20 mL of the modified MXene dispersion to obtain a molybdenum disulfide-MXene / biomass carbon composite aerogel.
[0051] Experimental test:
[0052] Figure 1 The XRD pattern of the molybdenum disulfide-MXene / biomass carbon composite aerogel prepared in Example 1 of the present invention is shown in FIG. Figure 1 It can be seen that the characteristic diffraction peaks of MoS2 (002), (100) and (110) appeared in the composite aerogel, indicating that MoS2 was successfully grown in the biomass carbon aerogel. The characteristic diffraction peaks of MXene did not appear, which is because the amount of MXene introduced is small and uniformly dispersed in the composite aerogel.
[0053] Figure 2 This is a scanning electron microscope image of the molybdenum disulfide-MXene / biomass carbon composite aerogel prepared in Example 1 of the present invention. As can be seen from the figure, the composite aerogel exhibits a continuous and uniform porous structure, and the flaky molybdenum disulfide grows uniformly and vertically on the surface of the composite aerogel.
[0054] Figure 3TEM image of the molybdenum disulfide-MXene / biomass carbon composite aerogel prepared in Example 1 of the present invention. As can be seen from the figure, the size of the grown molybdenum disulfide is about 500 nm.
[0055] Figures 4 - 5 Adsorption efficiency diagrams of the molybdenum disulfide-MXene / biomass carbon composite aerogel prepared in Example 1 of the present invention for cesium ions and strontium ions respectively. As can be seen from the figure, the adsorption capacities of the molybdenum disulfide-MXene / biomass carbon composite aerogel for cesium ions and strontium ions are 144.3 mg / g and 94.1 mg / g respectively, and under light conditions, the adsorption equilibrium time of the composite aerogel for cesium ions and strontium ions can be shortened from 4 hours to 2 hours. The molybdenum disulfide-MXene / biomass carbon composite aerogel can promote the synchronous adsorption of radioactive cesium ions and strontium ions based on solar energy.
[0056] The series of detailed descriptions listed above are only specific descriptions of the feasible embodiments of the present invention, and they are not intended to limit the protection scope of the present invention. Any equivalent embodiments or changes made without departing from the technical spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing molybdenum disulfide-MXene / biomass carbon composite aerogel, characterized in that: The following steps are involved: (1) Preparation of biomass carbon aerogel: chitosan is dispersed in an acetic acid solution, stirred and dissolved to obtain a chitosan dispersion, waste leather shavings hydrolyzate is added and stirred evenly, then a glutaraldehyde cross-linking agent is added to carry out a cross-linking reaction to obtain a chitosan hydrogel, and chitosan aerogel is obtained by freeze drying; then the chitosan aerogel is pyrolyzed in a tubular furnace at 400-800° C. under an inert gas atmosphere to obtain a biomass carbon aerogel; (2) Preparation of molybdenum disulfide / biomass carbon composite aerogel: The biomass carbon aerogel prepared in step (1) is immersed in a mixed solution of ammonium molybdate tetrahydrate and thiourea, and then sodium citrate is added, and the aerogel is placed in a reactor for hydrothermal reaction at 160-220° C. to obtain a molybdenum disulfide / biomass carbon composite aerogel; (3) Preparation of molybdenum disulfide-MXene / biomass carbon composite aerogel: First, MXene is added to deionized water and ultrasonically dispersed to obtain a MXene dispersion, polydiallyldimethylammonium chloride is added to positively modify the MXene, and then the molybdenum disulfide / biomass carbon composite aerogel prepared in step (2) is immersed in the modified MXene dispersion to obtain a molybdenum disulfide-MXene / biomass carbon composite aerogel.
2. The method for preparing the molybdenum disulfide-MXene / biomass carbon composite aerogel according to claim 1, characterized in that: In step (1), the mass ratio of chitosan to the hydrolyzate of waste leather scraps is (3-10):
1.
3. The method for preparing the molybdenum disulfide-MXene / biomass carbon composite aerogel according to claim 1, characterized in that: In step (2), the mass ratio of ammonium molybdate tetrahydrate to thiourea is 1:(1-5); and / or the ratio of the mass of the biomass carbon aerogel to the sum of the masses of ammonium molybdate tetrahydrate and thiourea is 1:(30-110).
4. The method for preparing the molybdenum disulfide-MXene / biomass carbon composite aerogel according to claim 1, characterized in that: In step (2), the mass ratio of biomass carbon aerogel to sodium citrate is 1:(0.5-1.5).
5. The method for preparing the molybdenum disulfide-MXene / biomass carbon composite aerogel according to claim 1, characterized in that: The concentration of the MXene dispersion in step (3) is 0.01-3 mg / L.
6. The method for preparing the molybdenum disulfide-MXene / biomass carbon composite aerogel according to claim 1, characterized in that: The solid-liquid ratio of the mixed solution of ammonium molybdate tetrahydrate and thiourea in step (2) is 1 g: (20-50) mL; and / or the solid-liquid ratio of the molybdenum disulfide / biomass carbon composite aerogel and the modified MXene dispersion in step (3) is 1 g: (50-100) mL.
7. The method for preparing the molybdenum disulfide-MXene / biomass carbon composite aerogel according to claim 1, characterized in that: In step (1), the chitosan aerogel is placed in a tubular furnace at 400-800°C and N2 atmosphere at 5°C·min -1 The heating rate is pyrolysis for 2-8h.
8. A molybdenum disulfide-MXene / biomass carbon composite aerogel, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.
9. An adsorbent, characterized in that It includes the molybdenum disulfide-MXene / biomass carbon composite aerogel described in claim 8.
10. Use of the molybdenum disulfide-MXene / biomass carbon composite aerogel according to claim 8 in the treatment of radioactive wastewater containing cesium ions and strontium ions.
Citation Information
Patent Citations
Method for preparing flexible electromagnetic shielding nanofiber film based on waste leather scrap hydrolysate
CN112853746A
Preparation method of modified chitosan-based carbon aerogel for capturing CO2
CN113797897A
Preparation method and application of biomass MoS2 / C-based solar energy absorbing material
CN116253389A
Carbon fiber-based solar photo-thermal efficient conversion material with excellent mechanical property as well as preparation method and application of carbon fiber-based solar photo-thermal efficient conversion material
CN116768309A
Carbon aerogel / MXene composite material as well as preparation method and application thereof
CN118405748A